Comprehensive Prediction of Thermosyphon Characteristics in Reactor Passive Cooling System Simulation Loop FASSIP-01 - H. Tjahjono (PPIKSN-BATAN, 2017)
Passive cooling mechanism for a nuclear reactor has been proven to be very important since the Fukushima Daiichi Reactor accident that was caused by active cooling system malfunction due to total loss of electrical power source. In the Center for Nuclear Reactor Technology and Safety of BATAN, the cooling mechanism was studied by using a natural circulation test loop named FASSIP-01 that applied thermosyphon mechanism of water inside pipes of 1” diameter. This study aimed to analytically predictthe thermal characteristics of the loop including its response time towards steady condition usingthe MATLAB calculation program. This prediction derived the influence of several parameters such as the heat transfer coefficient of the cooler side (h-cooler), the heater power, the elevation difference between the heater and cooler(DZ), and the effects of the insulation thickness of pipe (IT) on the flowrate, temperature, and the heat power distribution across all components in the loop. The result showed that byavoiding boiling condition, for transferring the heater power of 1000 W and 2000 W,the needed h-cooler exceeds 200 and 400 W m-2°C-1, respectively. For a h-cooler of 200 W m-2°C-1, the circulation flow rate increased from 0.04 to 0.06 kg/s-1 for heater power increase from 1000 W to 2000 W. Those flow rates were decreased to 0.037 and 0.052 kgs-1 by increasing h-cooler to 1000 W m-2°C-1.The results were in agreement with other studies on rectangular loops in the literature.The time needed to reach 95 % towards steady state was predicted to be more than 13 hours. Reduction of this time to less than five hours was possible by reducing the heater tank volume from 100 L to 30 L or by modifying the starting heater input power.